2020
DOI: 10.1186/s12940-020-00680-0
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in Yusho patients exposed to polychlorinated biphenyls and polychlorinated dibenzofurans: a 50-year retrospective cohort study

Abstract: Background In 1968, the Yusho incident resulted in accidental exposure to polychlorinated biphenyls (PCBs), polychlorinated dibenzofurans (PCDFs), and related compounds in Japan. This study updated the risk of mortality in Yusho patients. Methods We obtained updated cohort data for all Yusho patients for the period 1968–2017. We calculated standardized mortality ratios (SMRs) for all-cause and cause-specific mortality over a 50-year follow-up perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The occurrence of several chronic diseases, such as endocrine dysfunction, type 2 diabetes, cardiovascular disease, obesity, liver disorders, and neurological deficits, have been associated with exposure to PCBs [ 33 ]. Moreover, they affect the immune, reproductive, nervous and endocrine systems and are carcinogenic [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of several chronic diseases, such as endocrine dysfunction, type 2 diabetes, cardiovascular disease, obesity, liver disorders, and neurological deficits, have been associated with exposure to PCBs [ 33 ]. Moreover, they affect the immune, reproductive, nervous and endocrine systems and are carcinogenic [ 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Positive associations were suggested for non-Hodgkin lymphoma and breast cancer, but evaluation found limited evidence for the carcinogenicity of PCBs in humans. Notable epidemiological evidence in Japan came from a cohort study of Yusho patients, who experienced a mass food poisoning incident from cooking oil accidentally contaminated with PCBs, polychlorinated dibenzofurans (PCDFs), and other dioxin-related compounds in 1968: a recent 50-year follow-up study of these patients showed a significant increase in standardized mortality ratio for all cancers, and for lung cancer in men and liver cancer in women [ 30 ]. Blood concentrations of some PCB congeners were approximately 3–4 times higher than in the normal control group even 35 years after exposure [ 31 ].…”
Section: Organochlorine Pesticidesmentioning
confidence: 99%
“…In Japan, there was another considerable polychlorinated hydrocarbon exposure, which led to one of the biggest food poisonings in the world. This event, known as the "Yusho" incident, resulted from the mass contamination of rice bran oil with polychlorinated hydrocarbons [98]. The detrimental effects of chloracnegens are brought about by their immune suppression, carcinogenicity, and endocrine disruption [99].…”
Section: Chloracnementioning
confidence: 99%